Measurement and spatial difference of agricultural green development level in Guangxi - Qin, Quan (Bulletin of Applied Mathematics and Mathematics Education, 2021)
Green development of agriculture is the foundation of the entire green development. As a big agricultural province, promoting the green development of agriculture is conducive to promoting the high-quality development of agriculture and rural revitalization in Guangxi. This paper firstly analyzes the domestic and foreign scholars' research on the green development of agriculture, combined with the relevant policy theory, constructs the index system from the three aspects of green production, economic benefits and living standards, and then uses the entropy method to calculate the index weight and the comprehensive score of the green development of Agriculture in Guangxi, it analyzes the development trend of agricultural green development in Guangxi from 2010 to 2019 and the spatial differences of agricultural green development in 14 cities of Guangxi in 2019 afterwards. Finally, the following conclusions are drawn: the agricultural green development in Guangxi is on the rise from 2010 to 2019, but the development of green production is still in stagnancy; the overall level of Guangxi's agricultural green development in 2019 is relatively low, the best comprehensive developed cities are Guilin and Yulin, while the Hechi got the worst comprehensive score. According to the above conclusion, Guangxi should increase investment in science and technology to promote green agricultural production, focus on the overall development of the city to achieve regional coordination, give full play to the linkage effect of the city, and encourage well-developed cities to drive the development of surrounding cities.